2018
DOI: 10.1007/s00484-018-1512-8
|View full text |Cite
|
Sign up to set email alerts
|

Pan European Phenological database (PEP725): a single point of access for European data

Abstract: The Pan European Phenology (PEP) project is a European infrastructure to promote and facilitate phenological research, education, and environmental monitoring. The main objective is to maintain and develop a Pan European Phenological database (PEP725) with an open, unrestricted data access for science and education. PEP725 is the successor of the database developed through the COST action 725 "Establishing a European phenological data platform for climatological applications" working as a single access point f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
134
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 37 publications
4
134
0
Order By: Relevance
“…Phenological data for the five temperate tree species (Table S1) were obtained from the Pan European Phenology (PEP) network which provides an open access to in situ phenology records across Europe (http://www.pep725.eu; Templ et al., ). The leaf unfolding dates were defined according to the BBCH code (Biologische Bundesanstalt, Bundessortenamt und CHemische Industrie) (Meier, ), where the timing of spring leaf unfolding is expressed as the day of year (DOY).…”
Section: Methodsmentioning
confidence: 99%
“…Phenological data for the five temperate tree species (Table S1) were obtained from the Pan European Phenology (PEP) network which provides an open access to in situ phenology records across Europe (http://www.pep725.eu; Templ et al., ). The leaf unfolding dates were defined according to the BBCH code (Biologische Bundesanstalt, Bundessortenamt und CHemische Industrie) (Meier, ), where the timing of spring leaf unfolding is expressed as the day of year (DOY).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, at the beginning of this renewed research there was a latent accusation of a publication bias, or cherry picking, in the sense that only the most advancing records or extraordinary changes found their way into popular scientific journals. Therefore, the COST725 initiative collected all available European phenological data (later developed as the PEP725 database, Templ et al, ) and analysed more than 100,000 time series for climate change‐driven changes (Menzel, Sparks, Estrella, Koch, et al, , hereafter referred as GCB2006). The GCB2006 study concluded that there was indeed a strong response in European phenology to climate change and that these changes matched the warming pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Initial development of the Plant Phenology Ontology (PPO; Stucky et al., ) and associated informatics pipelines (see https://github.com/biocodellc/ppo-data-pipeline and https://github.com/biocodellc/ontology-data-pipeline) have made it possible to integrate heterogeneous plant phenological data from different global observation networks. Using these tools, an integrated phenology knowledge base has been developed that consolidates data from the National Phenology Network (NPN, Rosemartin et al., ; https://www.usanpn.org/), the National Ecological Observatory Network (NEON, Elmendorf et al., ; http://data.neonscience.org/), and the Pan‐European Phenology Database (PEP725, Koch et al., ; Templ et al., ; http://www.pep725.eu/). Data in this knowledge base can be accessed via a web portal (http://www.plantphenology.org) and an R package (https://cran.r-project.org/web/packages/rppo/).…”
mentioning
confidence: 99%
“…Phenology shifts over time are often the most immediate and visible ecological response to environmental change, and as a result, can serve as a "canary in the coal mine" for more drastic ecosystem changes (Parmesan and Yohe, 2003;Menzel et al, 2006;Cleland et al, 2007;Intergovernmental Panel on Climate Change, 2007;Wolkovich et al, 2012;Chuine and Régnière, 2017). Given the need to understand how phenology is changing in response to human pressure, monitoring programs have been set up at regional and continental scales to provide the evidential basis for detecting change (Koch et al, 2010;Rosemartin et al, 2014;Elmendorf et al, 2016;Templ et al, 2018). However, as noted recently (Kissling et al, 2018;Stucky et al, 2018), such systems often have different reporting standards and procedures, which can make broader-scale interoperability a challenge.…”
mentioning
confidence: 99%
See 1 more Smart Citation